Early Growth Response 3 (Egr3) Contributes a Maintenance of C2C12 Myoblast Proliferation. Issue 5 (12th October 2016) - Kurosaka, Mitsutoshi; Ogura, Yuji; Funabashi, Toshiya; Akema, Tatsuo
Abstract : Satellite cell proliferation is a crucially important process for adult myogenesis. However, its regulatory mechanisms remain unknown. Early growth response 3 (Egr3) is a zinc‐finger transcription factor that regulates different cellular functions. Reportedly, Egr3 interacts with multiple signaling molecules that are also known to regulate satellite cell proliferation. Therefore, it is possible that Egr3 is involved in satellite cell proliferation. Results of this study have demonstrated that Egr3 transcript levels are upregulated in regenerating mouse skeletal muscle after cardiotoxin injury. Using C2C12 myoblast culture (a model of activated satellite cells), results show that inhibition of Egr3 by shRNA impairs the myoblast proliferation rate. Results also show reduction of NF‐кB transcriptional activity in Egr3‐inhibited cells. Inhibition of Egr3 is associated with an increase in annexin V + cell fraction and apoptotic protein activity including caspase‐3 and caspase‐7, and Poly‐ADP ribose polymerase. By contrast, the reduction of cellular proliferation by inhibition of Egr3 was partially recovered by treatment of pan‐caspase inhibitor Z‐VAD‐FMK. Collectively, these results suggest that Egr3 is involved in myoblast proliferation by interaction with survival signaling. J. Cell. Physiol. 232: 1114–1122, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Egr3 maintains myoblast proliferation by stabilizing basal NF‐κB activity. However, the inhibition of Egr3 results in activation of apoptotic signaling by suppressing NF‐κB activity. The activation of apoptotic signaling is associated with proliferation defect in myoblast.